2013
DOI: 10.1371/journal.pgen.1003284
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Gene–Environment Interactions between Common Breast Cancer Susceptibility Loci and Established Environmental Risk Factors

Abstract: Various common genetic susceptibility loci have been identified for breast cancer; however, it is unclear how they combine with lifestyle/environmental risk factors to influence risk. We undertook an international collaborative study to assess gene-environment interaction for risk of breast cancer. Data from 24 studies of the Breast Cancer Association Consortium were pooled. Using up to 34,793 invasive breast cancers and 41,099 controls, we examined whether the relative risks associated with 23 single nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
149
2
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 151 publications
(163 citation statements)
references
References 40 publications
(70 reference statements)
8
149
2
4
Order By: Relevance
“…28 Consortium-based analyses may be particularly useful for detecting variants modified by weak-tomoderate gene-environment interactions. 29 Meta-analysis has also become increasingly popular in GWAS, 30 where it can aid in exploring the heterogeneity across data sets and identifying more disease-related genes. 31 In 2011, there were 173 publications on metaanalyses and pooled analyses of candidate genes in cancer, and 39 GWAS, of which 6 included a meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…28 Consortium-based analyses may be particularly useful for detecting variants modified by weak-tomoderate gene-environment interactions. 29 Meta-analysis has also become increasingly popular in GWAS, 30 where it can aid in exploring the heterogeneity across data sets and identifying more disease-related genes. 31 In 2011, there were 173 publications on metaanalyses and pooled analyses of candidate genes in cancer, and 39 GWAS, of which 6 included a meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The general approach to work around this problem has been to assume that these factors act independently in modifying risk, unless evidence to the contrary is observed. Although statistical power to detect deviations from log-additive combined effects is limited, studies in the general population have consistently found very little evidence of these (Milne et al 2010a,b, Travis et al 2010, Campa et al 2011, Nickels et al 2013, Rudolph et al 2015. Prospective studies will be essential to assess the validity of this assumption and of the risk prediction models more generally.…”
Section: :10mentioning
confidence: 99%
“…1 The mechanism of breast carcinogenesis is still not fully understood, but breast cancers are generally considered to result from interactions between multiple environmental, dietary, hereditary, racial and socioeconomic risk factors. 2 Aurora kinase A, which is encoded by the STK15 gene (also known as BTAK), is involved in cell-cycle regulation, in particular the passage from G 2 to M, through the formation of mitotic spindles. 3 Due to this regulatory function, the STK15 gene has been hypothesized to be a potential cancer susceptibility gene.…”
Section: Introductionmentioning
confidence: 99%